Inertial cavitation at the nanoscale - Kwan, J; Graham, S; Coussios, C (2013)
Our group has recently developed novel nano-sized drug carriers that spatially target a tumour and release their payload in the presence of ultrasound-induced inertial cavitation. To maximize drug release and distribution within the tumour, co-localisation of the drug carrier and cavitation nuclei is necessary. We have recently demonstrated that rough-patterned silica nanoparticles can reduce inertial cavitation thresholds to clinically relevant levels, and will extravasate in tumours alongside the liposomes by virtue of their size. We now report on the underlying mechanisms that these nanoparticles, which are orders of magnitude smaller than the acoustic wavelength, can instigate inertial cavitation. The rough surface of the nanoparticle is modelled as a plane with a crevasse that traps a nanobubble. Using this model, we predict the motion of a gas bubble as it emerges from the cavity in response to the compressional and rarefactional ultrasonic pressures. We show that cavitation occurs when the nanobubble breaks free from the surface, growing unstably before collapsing during the compressional half cycle of the acoustic wave. Calculations show that a nanoscaled cavity greatly reduces the cavitation threshold across all frequencies and geometries studied. In addition, cavitation thresholds nonlinearly decrease with increasing cavity size. © 2013 Acoustical Society of America.